Legal madness in the nineteenth century - Bartlett, Peter (Oxford University Press, 2001)
Legal sources remain under-exploited in the history of madness, and the legal character of some documents is sometimes unrecognized. This article examines the interrelations between legal and medical histories of madness, and discusses use and availability of nineteenth-century legal source materials relating to criminal insanity, mental incapacity, and the confinement of the insane.